Boosting self‐assembly diversity in the solid‐state by chiral/non‐chiral ZnII‐porphyrin crystallization - Qian, Wenjie; González-Campo, Arántzazu; Pérez-Rodríguez, Ana; Rodríguez-Hermida, Sabina; Imaz, Inhaz; Wurst, Klaus; Maspoch, Daniel; Ruiz, Eliseo; Ocal, Carmen; Barrena, Esther; Amabilino, David B.; Aliaga-Alcalde, Núria (Wiley-VCH Verlag, 2018)
This work bases on the solid‐state study of a chiral ZnII‐porphyrin derivative (5,10,15,20‐tetra[(4‐R,R,R,R)‐methyl‐2‐phenoxy‐propanoate, 1) building block and its achiral analogous (2). Here, foreseen the rich molecular recognition of the designed metallo‐porphyrins (1 and 2) and tendency to crystallize, we recrystallized both using two sets of solvents (CH2Cl2/CH3OH and CH2Cl2/hexane). As a result, four different crystalline arrangements (1a‐b, 2a‐b, from 0D to 2D) were successfully achieved. We performed solid state studies for all the species, analysing the role played by chirality, solvent mixtures and surfaces (mica and HOPG), on the supramolecular arrangements. As for the combination of solvents and substrates we obtained a variety of micro‐sized species, from vesicles to flower‐shaped arrays, including geometrical microcrystals. Overall, our results emphasize the environmental susceptibility of metallo‐porphyrins and how this feature must be taken into account in their design.